2017
DOI: 10.2174/1874325001711010077
|View full text |Cite
|
Sign up to set email alerts
|

Latissimus Dorsi Transfer in Posterior Irreparable Rotator Cuff Tears

Abstract: Background:Massive rotator cuff tears pose a difficult and complex challenge even for the experienced surgeon; inability to repair these tears by conventional means designates them as irreparable, while management becomes quite taxing. Several operative options have been suggested for the management of such lesions with varying degrees of success, while it is imperative to match patient demands and expectations to the predicted outcome.Methods:Research articles are examined and key concepts are discussed, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 126 publications
0
12
0
Order By: Relevance
“… 2 Additionally, outcomes may be influenced by multiple elements such as age, pain, disability, functional demands, patient expectations, and willingness to adhere to lengthy rehabilitation protocols. 8 …”
mentioning
confidence: 99%
“… 2 Additionally, outcomes may be influenced by multiple elements such as age, pain, disability, functional demands, patient expectations, and willingness to adhere to lengthy rehabilitation protocols. 8 …”
mentioning
confidence: 99%
“…In the setting of an irreparable cuff tear and no osteoarthritis in younger patients, tendon transfers may improve shoulder function 6,50,94 . For posterosuperior tears, transfer of the latissimus dorsi 97 is the most common procedure.…”
Section: Tendon Transfermentioning
confidence: 99%
“…For posterosuperior tears, transfer of the latissimus dorsi 97 is the most common procedure. Careful patient selection is required and patients with pseudoparalysis and insufficient subscapularis function probably have much less gain from this procedure 6,94,214 . The variability of results, and the fact that the transferred latissimus tendon provides a quite vertical pull, have led to the development of the lower trapezius transfer 72 , in which the transferred lower trapezius, and the allograft that is required, provide a line of pull that is nearly identical to that of infraspinatus 50 .…”
Section: Tendon Transfermentioning
confidence: 99%
“…Several studies have investigated preoperative factors that affect the clinical outcomes of latissimus dorsi transfer for MIRCTs. 1,8,17,24,29,50 Anastasopoulos et al 1 suggested that patients with irreparable posterior-superior rotator cuff tears with associated atrophy or fatty degeneration of the subscapularis and deltoid, as well as a large critical shoulder angle, are more likely to have poor clinical outcomes. Successful outcomes were associated with a preoperative critical shoulder angle of ≤36°.…”
Section: Latissimus Dorsi Transfermentioning
confidence: 99%
“…8,10,29,[33][34][35]42,50 Indications for this procedure include younger patients who are suffering from severe functional disabilities caused by an irreparable posterior-superior rotator cuff tear and patients with minimal to no glenohumeral arthritis. 1,34,43 Numerous studies have discussed functional and clinical outcomes after latissimus dorsi transfer for MIRCTs (see Table 1). § One study 24 evaluated the functional outcome scores of 46 cases in which open transfer was performed.…”
Section: Latissimus Dorsi Transfermentioning
confidence: 99%